Regulation of pattern formation in the Drosophila hindgut by wg, hh, dpp, and en. - Takashima, S.; Murakami, R. (Mechanisms of Development, 2001)
The hindgut of the Drosophila embryo is subdivided into three major domains, the small intestine, large intestine, and rectum, each of which is characterized by specific gene expression. Here we show that the expression of wingless (wg), hedgehog (hh), decapentaplegic (dpp), and engrailed (en) corresponds to the generation or growth of particular domains of the hindgut. wg, expressed in the prospective anal pads, is necessary for activation of hh in the adjacent prospective rectum. hh is expressed in the prospective rectum, which forms anteriorly to the anal pads, and necessary for the expression of dpp at the posterior end of the adjacent large intestine. wg and hh are also necessary for the development of their own expression domains, anal pads, and rectum, respectively. dpp, in turn, causes the growth of the large intestine, promoting DNA replication. en defines the dorsal domain of the large intestine, repressing dpp in this domain. A one-cell-wide domain, which delineates the anterior and posterior borders of the large intestine and its internal border between the dorsal and ventral domains, is induced by the activity of en. We propose a model for the gene regulatory pathways leading to the subdivision of the hindgut into domains.